Seed storage behaviour in Berberis aristata - MUKHOPADHYAY, DEBARATI; CHAUHAN, J C; PARIHAR, S S; DADLANI, MALAVIKA (The Indian Journal of Agricultural Sciences, 2013)
Berberis aristata DC (of Berberidaceae) is commonly known as Daruharidra or Daruhaldi. It is one of the most valuable medicinal plants in Indian system of medicine. No information is available on seed morphology, dormancy and seed storage behavior of the species which is required for conserving the seeds in seed banks. Therefore an experiment was conducted with seed lot collected from Almora, Uttarakhand. Studies were conducted on seed germinability (using germination tests) and seed viability (using topographical tetrazolium chloride test) in relation to desiccation and chilling tolerance using a factorial combination of four moisture content (5, 7, 10 and 12% moisture content in seeds on fresh weight basis), three storage temperatures (seeds stored in ambient condition, at 15°C and at –20°C) and five storage periods (0, 3, 6, 9 and 12 months). Perusal of data revealed that no significant loss in germination was observed in seeds with 5 and 7% moisture content under ambient as well as other storage conditions, suggesting that seeds of Berberis aristata are desiccation as well as chilling tolerant and exhibited orthodox seed storage behavior. The seeds are ideal for ex situ conservation in seed banks/ gene banks for a longer period.